Holistic (agroecological) business model assessment: Agricultural Cooperative of Aromatic Cacao Colpa de Loros in Peru - Narjes, Manuel Ernesto; Parra, Ernesto (CGIAR System Organization, 2022)
The production of cacao (Theobroma cacao) in agroforestry arrangements is one of the sustainable land use systems conceived within the ecological corridor that is being promoted along the Aguaytía river basin, as part of the Regional Government of Ucayali’s (GOREU) Plan for the Sustainable Economic Development of the department towards 2050. The importance of cacao production as a main livelihood for many of the small producers along Ucayali’s ecological corridor justifies a first focus on the cocoa value chain as an entry strategy for agroecology in the territory. The participants of AE-I’s (i.e., CGIAR’s Agroecology Initiative) launch workshop that took place in July 2022 nevertheless emphasized their interest in addressing the agroecological transition at the farm level, that is, with a holistic approach that does not exclusively focus on the cultivation of cacao and/or other cash crops. This opens the future possibility of exploring for BM opportunities in “secondary” candidate value chains that result from integrating agroecological principles in the cultivation of cacao (e.g., cacao-plantain intercropping).